2015
DOI: 10.1002/ejp.803
|View full text |Cite
|
Sign up to set email alerts
|

A small yet comprehensive subset of human experimental pain models emerging from correlation analysis with a clinical quantitative sensory testing protocol in healthy subjects

Abstract: When basing a selection of a small comprehensive set of pain models on the assumption that highly correlated pain measures account for redundant results and therefore, one member of each group suffices an economic yet comprehensive pain study, results suggest inclusion of established C-fibre, Aδ-fibre mediated and thermal pain measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The battery of evoked pain tasks was not sensitive to detect analgesic effects of paracetamol, but that finding by itself provides information on the much debated and yet unrevealed pharmacological mechanism of action, as we are able to compare the results to other compounds with known mechanism of action. As recognized before (Lotsch et al., , ; van Amerongen et al., ), translatability of findings from human evoked pain models to clinical pain remains elusive. Nonetheless, if used prudently, this battery of pain tasks can provide invaluable information on pharmacodynamic and pharmacokinetic relationships in the early phases of drug development, especially when combined with other neurocognitive assessments.…”
Section: Discussionmentioning
confidence: 98%
“…The battery of evoked pain tasks was not sensitive to detect analgesic effects of paracetamol, but that finding by itself provides information on the much debated and yet unrevealed pharmacological mechanism of action, as we are able to compare the results to other compounds with known mechanism of action. As recognized before (Lotsch et al., , ; van Amerongen et al., ), translatability of findings from human evoked pain models to clinical pain remains elusive. Nonetheless, if used prudently, this battery of pain tasks can provide invaluable information on pharmacodynamic and pharmacokinetic relationships in the early phases of drug development, especially when combined with other neurocognitive assessments.…”
Section: Discussionmentioning
confidence: 98%
“…While innocuous ("warm") and noxious ("heat") sensations are initially transmitted by different peripheral receptors, 41 their thresholds in humans are correlated. 42 thus suggesting a common cerebral system of integration. This has been confirmed by human fMRI studies which have identified brain regions that are sensitive to heat intensity regardless of pain intensity.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the potential use of human experimental pain models for analgesic drug research, we applied a clinically established QST battery that was originally developed to phenotype neuropathic pain in patients, which was also successfully used in a human experimental context on healthy subjects. 18 , 45 , 46 To extract meaningful information from the resulting high-dimensional data, we applied machine-learning techniques with the aims of (1) identifying the most relevant effects of UV-B and topical capsaicin on QST parameters and (2) identifying possible subgroups of subjects who share similar QST responses to selected hypersensitization treatments. The results of these analyses indicated that (1) both UV-B– and capsaicin-induced experimental hypersensitization primarily increased subjects' sensitivity to heat; (2) UV-B additionally modulated sensitivity to cold; (3) subgroups of responders to topical application of capsaicin differed with respect to their sensitivity to pressure pain, and this could be attributed to sex differences; and (4) the response to the UV-B hypersensitization treatment was heterogeneous and included a group of nonresponders, which in the high-dimensional space of the QST pattern was indistinguishable from the absence of any hypersensitization treatment.…”
Section: Discussionmentioning
confidence: 99%